Crystal structure of Jararacussin-I: The highly negatively charged catalytic interface contributes to macromolecular selectivity in snake venom thrombin-like enzymes - Ullah, A. [UNESP]; Souza, T. A C B; Zanphorlin, L. M. [UNESP]; Mariutti, R. B. [UNESP]; Santana, V. S. [UNESP]; Murakami, M. T.; Arni, R. K. [UNESP] (Wiley, 2013)
Snake venom serine proteinases (SVSPs) are hemostatically active toxins that perturb the maintenance and regulation of both the blood coagulation cascade and fibrinolytic feedback system at specific points, and hence, are widely used as tools in pharmacological and clinical diagnosis. The crystal structure of a thrombin-like enzyme (TLE) from Bothrops jararacussu venom (Jararacussin-I) was determined at 2.48 Å resolution. This is the first crystal structure of a TLE and allows structural comparisons with both the Agkistrodon contortrix contortrix Protein C Activator and the Trimeresurus stejnegeri plasminogen activator. Despite the highly conserved overall fold, significant differences in the amino acid compositions and three-dimensional conformations of the loops surrounding the active site significantly alter the molecular topography and charge distribution profile of the catalytic interface. In contrast to other SVSPs, the catalytic interface of Jararacussin-I is highly negatively charged, which contributes to its unique macromolecular selectivity. © 2012 The Protein Society.
Keywords: Bothrops jararacussu; Crystal structure; Jararacussin-I; Thrombin-like enzyme; Agkistrodon contortrix contortrix Protein C Activator; enzyme activator; jararacussin 1; plasminogen activator; snake venom; Trimeresurus stejnegeri plasminogen activator; unclassified drug; amino acid composition; catalysis; crystal structure; macromolecule; priority journal